Association of sugar consumption with risk of depression and anxiety: a systematic review and meta-analysis - Xiong, JiaHui; Wang, Lu; Huang, HongLu; Xiong, San; Zhang, ShiPeng; Fu, QinWei; Tang, Rui; Zhang, QinXiu (Frontiers in Nutrition, 2024)
Background: Sugar consumption has increased dramatically around the world, and at the same time, the prevalence of mental illnesses such as depression and anxiety continues to increase. While previous research has explored the impact of various dietary factors on mental health, the specific impact of dietary sugar consumption on the risk of depression and anxiety disorders remains elusive.This study aimed to comprehensively assess this relationship through a systematic review and metaanalysis.Methods: The PubMed, Embase, Cochrane library, web of science, China National Knowledge Network (CNKI) and WangFang were Systematically searched for the studies of the association between total dietary sugar intake and risk of depression and/or anxiety. The articles that meet the criteria are screened and included in the systematic review, and the data is extracted after assessing their quality. Stata18.0 software was used for the meta-analysis.Results: 40 studies with 1,212,107 participants were included in the analysis. Results showed that sugar intake increased the risk of depression by 21% (OR= 1.21,95% CI: 1.14,1.27), while the overall association between sugar intake and anxiety risk was not statistically significant (OR=1.11, 95%CI:0.93,1.28). Despite high heterogeneity (I²= 99.7%), the results were statistically significant (P < 0.000). Subgroup analyses showed that the association between sugar consumption and depression risk remains consistent across different study designs (cross-sectional, cohort and case-control studies) and different sample sizes (< 5000, 5000-10000, > 10000). Women have a higher risk of depression than men (OR = 1.19, 95% CI: 1.04, 1.35). Among the different exposure measures, the Food Frequency Questionnaire (FFQ) showed the most significant effect (OR = 1.32, 95% CI: 1.08, 1.67, I² = 99.7%, P < 0.000). Through the measuringdiagnostic tool of subgroup analysis showed that there were significant correlation between sugar intake and risk of depression, PHQ-9 (OR = 1.29, 95%CI: